PENGARUH KEPUASAN WAJIB PAJAK, PENEGAKAN SANKSI PAJAK DAN KEADILAN DISTRIBUTIF TERHADAP KEPATUHAN WAJIB PAJAK DI KOTA PONTIANAK - JOKO SUSENO; SANI SANI (STIE 'INDONESIA' Pontianak, 2018)
The aims of study are analyzing the impact of satisfaction from the taxpayers, tax sanction enforcement and distributive justice on taxpayer compliance, especially taxpayer of construction service companies. Data has been collected by closed questionnaire with Likert scale between 1 and 5. From the statement, it can know the level of taxpayer compliance as the respondent to the problem determined by the way of providing value to answers result from the respondents. Multiple regression analysis has been used to analyze data. Based on the research, it shows that taxpayer satisfaction variable can be proved by having a positive and significant influence on taxpayer compliance especially taxpayer of construction service company by coefficient result β = 0,383 with p-value equal to 0,0095 smaller than α= 0,05 , variables Enforcement of tax sanctions has been proven by having a positive and significant impact on taxpayer compliance, especially Construction Services Company coefficient β = 0.943 with p-value of 0.014 smaller than α = 0.05. And distributive justice variable has positive and significant influence on taxpayer compliance especially Construction Service Company with result of coefficient β = 0,749 with p-value equal to = 0,0185 smaller than α = 0, 05